Differential Redox State Contributes to Sex Disparities in the Response to Influenza Virus Infection in Male and Female Mice - Celestino, Ignacio; Checconi, Paola; Amatore, Donatella; De Angelis, Marta; Coluccio, Paolo; Dattilo, Rosanna; Alunni Fegatelli, Danilo; Clemente, Ann Maria; Matarrese, Paola; Torcia, Maria Gabriella; Mancinelli, Romina; Mammola, Caterina Loredana; et al. (Frontiers in Immunology, 2018)
Influenza virus replicates intracellularly exploiting several pathways involved in the regulation of host responses. The outcome and the severity of the infection are thus strongly conditioned by multiple host factors, including age, sex, metabolic and redox conditions of the target cells. Hormones are also important determinants of host immune responses to influenza, and are recently proposed in the prophylaxis and treatment. The present study shows that female mice are less susceptible than males to mouse-adapted influenza virus (A/PR8/H1N1). Compared with males, PR8-infected females display higher survival rate (+36%), milder clinical disease and less weight loss. They also have milder histopathological signs, especially free alveolar area is higher than that in males, even if pro-inflammatory cytokine production shows slight differences between sexes; hormone levels, moreover, do not vary significantly with infection in our model. Importantly, viral loads (both in terms of viral M1 RNA copies and TCID50) are lower in PR8-infected females. An analysis of the mechanisms contributing to sex disparities observed during infection reveals that the female animals have higher total antioxidant power in serum and their lungs are characterized by increase in i) the content and biosynthesis of glutathione, ii) the expression and activity of antioxidant enzymes (peroxiredoxin 1, catalase and glutathione peroxidase), iii) the expression of the anti-apoptotic protein Bcl-2. In contrast, infected males are characterized by high expression of NOX4 oxidase and phosphorylation of p38 MAPK, both enzymes promoting viral replication. All these factors are critical for cell homeostasis and susceptibility to infection. Reappraisal of the importance of the host-cell redox state and sex-related effects may be useful in the attempt to develop more tailored therapeutic interventions in the fight against influenza.